First phylogeny of the shredder caddisfly genus Phylloicus Müller, 1880 (Trichoptera: Calamoceratidae) - Vilarino, Albane (2025)
Phylloicus is the most diverse calamoceratid caddisfly genus in the Neotropics; here the first phylogeny for the genus is inferred based on a Bayesian analysis of 105 morphological characters and COI barcoding. Results support the monophyly of Phylloicus and the close affinity to Anisocentropus (primarily Oriental and Australasian). The results recovered two of three previously proposed species groups: the P. chalybeus Group (Antillean species) and P. aeneus Group (Mesoamerican species). We propose P. bromeliarum Group, characterized by species with triangular preanal appendages. Palaeobiogeographic considerations suggest that Phylloicus likely radiated in the Palaeocene after the breakup of the austral trans-Antarctic connection and the formation of modern tropical forests. Additionally, Phylloicus camboim sp. nov. is described based on adult males collected in a forested fragment in the Cerrado savanna of southeastern Brazil and placed in the P. bromeliarum Group. The results also indicate that the corematic pheromone structures and the modified sternum IX withdrawn into sternum VIII evolved several times independently. http://zoobank.org/urn:lsid:zoobank.org:pub:9800A711-3039-4C8C-9EFC-E67D50B0B153.